Analisis Kelembagaan Petani dalam Mendukung Keberfungsian Infrastruktur Irigasi (Studi Kasus: Daerah Irigasi Batang Anai, Sumatera Barat) - Aini, Yenni Nur; Nadida, Zafira (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
Until the year 2013, extensive damage to the national irrigation network reaches more than 2.85 million Ha. In addition, the depreciation of the irrigation network functions into non paddy rice field area of 40.000 ha recorded per year. These conditions indicate a malfunction of the built and operated irrigation infrastructure. If not handled properly, the government plans to meet national food surplus targeted cannot be fulfilled. To overcome these problems, the government is trying to improve the performance of irrigation infrastructure through a variety of programs and policy initiatives; one of which is to increase the activity of institutional/organizational farmers in operation and maintenance. Based on that, this study aims to analyze the institutional functioning of farmers to increase irrigation infrastructure. This research was conducted in May - November 2013 taken place in Batang Anai Irrigation Area, Padang, West Sumatra. The method of research used a qualitative approach and descriptive analysis techniques to the analysis of institutional conditions of farmers in Batang Anai, Padang, West Sumatra. The results show that the institutional conditions of farmers to encourage the functioning of the irrigation infrastructure in DI Anai indicated by three indicators, namely: 1) the number of active farmers’ organizations, 2) the number of active members of farmers’ organizations, and 3) the level of participation of farmers’ organizations in management of irrigation infrastructure. The analysis also showed that the number of organizations, the number of active members of the organization, and the level of participation in the study site showed quite good performance, which the activity of farmer’s organization has reached 87.59% or contributed 15.77% to support the function of infrastructure